2013
DOI: 10.1590/s1806-83242013005000017
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal factors associated with developmental defects of enamel in primary teeth: a case-control study

Abstract: The present study was designed to evaluate associations between developmental defects of enamel (DDE) in the primary dentition and aspects related to mothers and preschoolers in the city of Diamantina, Brazil. A case-control study was carried out involving children aged three to five years. The case group was composed of 104 children with at least one dental surface affected by DDE. The control group comprised 105 children without DDE, matched for gender and age. The diagnosis of enamel defects was performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 18 publications
1
17
0
14
Order By: Relevance
“…Em relação ao baixo peso do recém--nascido, alguns estudos observaram que os defeitos de esmalte mais encontrados foram as opacidades demarcadas nos incisivos e molares 16,36,37 .…”
Section: Baixo Peso Ao Nascerunclassified
See 2 more Smart Citations
“…Em relação ao baixo peso do recém--nascido, alguns estudos observaram que os defeitos de esmalte mais encontrados foram as opacidades demarcadas nos incisivos e molares 16,36,37 .…”
Section: Baixo Peso Ao Nascerunclassified
“…Crianças não amamentadas foram 3,2 vezes mais suscetíveis a serem afetadas por DDE quando comparadas com aquelas que foram amamentadas 5,37,38 . A ausência de amamentação é um importante fator predisponente ao aparecimento de DDE, porque faz com que a criança seja privada de substâncias nutricionais, como a vitamina D, necessárias para o seu desenvolvimento e, consequentemente, para a formação do esmalte 8 .…”
Section: Aleitamento Maternounclassified
See 1 more Smart Citation
“…International Publisher demonstrated that defects of enamel are deeply influenced by etiological factors that may be influencing already before the birth. 4 In preterm children, teeth are often more susceptible to caries and such alterations are often linked to an early onset GER: the severe hypocalcification of the dental tissues and the rapid onset of carious lesions strongly affect the esthetics of patients, with a negative impact also on social and psychological aspects. 5,6 In the light of this framework, our study has been aimed to investigate about the relationship between pediatric oral and systemic pathologies coexisting with preterm birth condition.…”
Section: Ivyspringmentioning
confidence: 99%
“…As interferências ocorridas durante a formação do esmalte são permanentemente registradas. Os defeitos de esmalte são definidos como distúrbios na formação e mineralização dos tecidos duros durante a odontogênese (21). As influências no desenvolvimento dentário podem afetar quantitativa e qualitativamente o desenvolvimento tanto do esmalte quanto da dentina (22,109 superfície lisa e espessura normal de esmalte (25,26).…”
Section: Aspectos Da Amelogêneseunclassified